2014
DOI: 10.1080/19440049.2013.871756
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the use of sarcosine, proline and glycine as acrylamide inhibitors in ripe olive processing

Abstract: The main purpose of this study was to evaluate the inhibitory effect on acrylamide (AA) formation and the impact on sensory characteristics in ripe olives of three selected amino acids (sarcosine, proline and glycine), which previously showed high AA inhibition rates in an olive model system. Each amino acid was separately added to packing solutions to give 100 or 200 mM at equilibrium, prior to a sterilisation treatment at 121°C. The results showed that sarcosine at 100 mM may be a good candidate for reducing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…92 Because heat sterilization of olives seems to be used to kill pathogenic microorganisms, it would be interesting to determine if adding natural broad-spectrum antimicrobials such as carvacrol, 93 to the processing medium would achieve the same objective without the need for heat treatment. 92 Because heat sterilization of olives seems to be used to kill pathogenic microorganisms, it would be interesting to determine if adding natural broad-spectrum antimicrobials such as carvacrol, 93 to the processing medium would achieve the same objective without the need for heat treatment.…”
Section: Reduction Of Acrylamide In Olivesmentioning
confidence: 99%
“…92 Because heat sterilization of olives seems to be used to kill pathogenic microorganisms, it would be interesting to determine if adding natural broad-spectrum antimicrobials such as carvacrol, 93 to the processing medium would achieve the same objective without the need for heat treatment. 92 Because heat sterilization of olives seems to be used to kill pathogenic microorganisms, it would be interesting to determine if adding natural broad-spectrum antimicrobials such as carvacrol, 93 to the processing medium would achieve the same objective without the need for heat treatment.…”
Section: Reduction Of Acrylamide In Olivesmentioning
confidence: 99%
“…Since 3,3 ,3 -nitrilotris is not as toxic as acrylamide, if conversion of acrylamide to 3,3 ,3 -nitrilotris occurred in vivo, this conversion could theoretically mitigate the toxicity of acrylamide, although that remains to be demonstrated. Other than 3-APA investigated in the current study, Sánchez, Beato, López-López, and Montaño (2014) reported amino acids could suppress the toxicity of acrylamide via the formation of adducts. Both 3-APA and amino acid contain amino groups which could react with acrylamide to form adducts through Michael addition.…”
Section: Cytotoxicity Of 33 3 -Nitrilotris Against Caco-2 Cellsmentioning
confidence: 76%
“…Acrylamide formed in black ripe olives was found to be stable during storage at room temperature for 6 months [5], but an acrylamide reduction of 25% has been determined after 8 months compared to its content after 20 days of storage [18]. Acrylamide concentrations significantly decreased during storage have been found in other foods like coffee, cacao, and roasted almonds, which was attributed to reactions of acrylamide with food components and/or reaction products [19,20].…”
Section: Influence Of Olive Cultivar and Processing Conditions On Acrmentioning
confidence: 96%
“…Consequently, Casado and Montaño [5] applied GC-MS with bromination to quantitate acrylamide in black ripe olives. Therefore, this method was also used in further investigations of this group [16][17][18]. Therefore, this method was also used in further investigations of this group [16][17][18].…”
Section: Gc-ms With Brominationmentioning
confidence: 99%